Classical to Relaxor Ferroelectric Transformation of Lanthanum Modified BaTi 0.91 Sn 0.09 O 3 Ceramics - Wiwat Pattanakasem; Sasipohn Prasertpalichat; Pathit Premwichit; Naratip Vittayakorn; Theerachai Bongkarn (Integrated ferroelectrics, 2023)
Lead-free Ba1-xLaxTi0.91Sn0.09O3 (BLTS) ceramics with x = 0, 0.01, 0.03 and 0.05, were prepared by the traditional solid-state sintering method with calcination and sintering temperatures of 1200 °C for 2 h and 1400 °C for 4 h, respectively. X-ray diffraction (XRD) measurements revealed that all the BLTS ceramics had pure perovskite structures with no detectable impurities. When x = 0 and 0.01, the ceramics exhibited coexisting orthorhombic (O) and tetragonal (T) phases, while the orthorhombic (O), tetragonal (T) and cubic phase (C) were detected in the BLTS ceramics with x = 0.03 and 0.05, which the Rietveld refinement analysis confirmed. Furthermore, increasing x in the BLTS ceramics led to a large decrease in the average grain size (from 45.7 to 0.9 µm). A significant decrease in the remnant polarization (Pr) accompanied by very slim hysteresis loops were observed for higher La (x ≥ 0.03) levels. This demonstrates that BLTS ceramics transition from classical ferroelectric to relaxor ferroelectric behavior due to changing occupancy of the A-site to La3+ from Ba2+.
Keywords: Ferroelectric and Piezoelectric Materials; Microwave Dielectric Ceramics Synthesis; Multiferroics and related materials